Healing Chains, Relationships of Power and Competing Religious Imageries in the Monastery of Saints Kosmas and Damian in Kuklen (Bulgaria) - Magdalena Lubanska (Journal of Ethnology and Folkloristics)
This article offers an anthropological analysis of a conflict over the use of a set of 'healing chains' and other focal objects kept in the Orthodox Christian monastery of Saints Kosmas and Damian in Kuklen, Bulgaria. In a nutshell, the conflict captures the leading religious imageries propagated by the custodians of the monastery on the one hand, and the spiritual leaders of a new religious movement, so-called Deunovians, on the other. The analysis helps situate some of the significant changes currently affecting the religious culture of Orthodox Christians in Bulgaria within a broader social and cultural context.